2007
DOI: 10.1038/ng1983
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome repression by localization of the C. elegans dosage compensation machinery to sites of transcription initiation

Abstract: Introductory paragraphAmong organisms with chromosome-based mechanisms of sex determination, failure to equalize expression of X-linked genes between the sexes is typically lethal. In C. elegans, XX hermaphrodites halve transcription from each X chromosome to match the output of XO males 1 . Here, we mapped the binding location of the condensin homolog DPY-27 and the zinc finger protein SDC-3, two components of the C. elegans dosage compensation complex (DCC) 2,3 . Strong foci of DCC binding were observed on X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
196
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(211 citation statements)
references
References 30 publications
11
196
3
1
Order By: Relevance
“…Consistent with extensive evidence that these proteins collaborate to repress expression of X-linked genes in XX hermaphrodites (Meyer 2005;Ercan et al 2007), their ChIP data sets show higher signals on the X chromosome than on autosomes (Supplemental Fig. S2), as observed previously for some of these factors (Ercan et al 2007(Ercan et al , 2009Jans et al 2009). Interestingly, two histone modifications, H3K27me1 and H4K20me1, also group with the dosage compensation proteins (Supplemental Fig.…”
Section: H3k27me3 Distribution Is Anti-correlated With Rna Levelssupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with extensive evidence that these proteins collaborate to repress expression of X-linked genes in XX hermaphrodites (Meyer 2005;Ercan et al 2007), their ChIP data sets show higher signals on the X chromosome than on autosomes (Supplemental Fig. S2), as observed previously for some of these factors (Ercan et al 2007(Ercan et al , 2009Jans et al 2009). Interestingly, two histone modifications, H3K27me1 and H4K20me1, also group with the dosage compensation proteins (Supplemental Fig.…”
Section: H3k27me3 Distribution Is Anti-correlated With Rna Levelssupporting
confidence: 88%
“…For an antibody to pass dot blot analysis required that at least 75% of the total signal be specific to the cognate peptide. Mouse monoclonal antibodies against H3K9me2 (clone 6D11), H3K9me3 (clone 2F3), H3K27me3 (clone1E7), H3K36me2 (2C3), and H3K36me3 (13C9) were gifts from Hiroshi Kimura (Osaka University) (Kimura et al 2008 , MES-4 (SDI SDQ0791) , SDC-3 and DPY-27 (Ercan et al 2007), DPY-26 and MIX-1 (Ercan et al 2009), and HTZ-1 (Whittle et al 2008). DPY-28 antibody was kindly provided by Kirsten Hagstrom.…”
Section: Methods Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The DCC is composed of a condensin I-like complex (known as condensin I DC ) and another five-subunit complex containing SDC-1, SDC-2, SDC-3, DPY-21, and DPY-30. Experiments combining genome-wide chromatin precipitation assays have revealed that the DCC is enriched at ;1500 sites scattered along the length of the X chromosomes that can be categorized into two different classes: rex (recruiting element on X) sites and dox (dependent on X) sites (McDonel et al 2006;Ercan et al 2007;Blauwkamp and Csankovszki 2009;Jans et al 2009). The rex sites contain a 12-base-pair sequence motif called MEX (motif enriched on X) and are able to recruit the DCC when detached from the X.…”
Section: Dosage Compensation In C Elegansmentioning
confidence: 99%